Republic of Poland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Financial System Stability Assessment discusses the findings of the IMF mission regarding assessing stability and performance of Polish financial systems. The banking system in the aggregate shows resilience to adverse shocks, although some medium-sized banks appear weak. For the financial system, sovereign-financial institution linkages have increased, while exposures to foreign-exchange mortgages have declined. Important shortcomings have been identified in prudential oversight reflecting budgetary constraints and a governance framework that compromises operational independence. Arrangements for crisis management are generally sound, although measures are required to strengthen the independence of the Bank Guarantee Fund and powers of the Polish Financial Supervision Authority. The Polish authorities have welcomed the IMF's and World Bank's comprehensive review of the supervisory and regulatory framework in Poland and provided feedback for every recommendation made in the report.